A systematic review of Instrumental Activities of Daily Living scales in dementia: room for improvement. Issue 1 (16th December 2008) - Sikkes, S A M; de Lange-de Klerk, E S M; Pijnenburg, Y A L; Scheltens, P; Uitdehaag, B M J
Abstract : Background: Instrumental Activities of Daily Living (IADL) questionnaires can be helpful in diagnosing dementia and are often used for clinical follow-up and treatment evaluation in dementia patients. Despite the large number of questionnaires, their quality has received little attention. Objective: To systematically review the measurement properties of all available structured informant-based (I)ADL questionnaires, developed or validated for use in demented patients. Methods: A systematic literature search was conducted in MEDLINE, PsycINFO and EMBASE for psychometric articles on (I)ADL questionnaires. In addition, reference lists of all retrieved articles were screened. Standardised criteria were used to assess the quality of the measurement properties. When possible, investigators were contacted to obtain missing information. Two authors independently extracted studies and performed the quality assessment of the questionnaires. Findings: Thirty-two articles were selected, covering 12 (I)ADL questionnaires. Information on 52.3% of the quality aspects was not available, 32.4% of the ratings were indeterminate, 8.1% were positive, and 7.2% were negative. Out of eight measurement properties, two scales (the DAD and the Bristol ADL) received two positive ratings and were classified as of moderate quality. Five scales (ADL-PI, ADL-IS, B-ADL, CSADL and Lawton IADL) received one positive rating. Interpretation: The findings indicate that improvements in and more data on psychometric properties of (I)ADL questionnaires for dementia patients are necessary in order to justify their use.